IMPLEMENTASI KEBIJAKAN BADAN USAHA MILIK DESA (BUMDes) DALAM PENGELOLAAN UNIT KELAPA TERPADU BUMDes SUMBER REZEKI DI DESA SUNGAI ARA TAHUN 2019 - Adji Aprindoko; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Village-Owned Enterprises are one of the institutions engaged in social and economic fields as well as as a service provider to rural communities, especially in the business sector. This study aims to determine how the management policy of the Sumber Sustenance Village Owned Enterprise (BUMDes) towards the Integrated Coconut Unit in Sungai Ara Village. This study uses a qualitative approach and types of descriptive data. The data used in this study are primary data and secondary data, primary data through interviews with resource persons and secondary data in the form of documents or data written by the author of Sumber Sustenance BUMDes related to the management of the Integrated Coconut Unit. Collecting data through interviews, observation, and documentation. The results showed that the implementation of the Sumber Sustenance BUMDes policy on the management of the integrated coconut unit in terms of communication was not optimal, the dissemination process of socialization did not reach the community, the quality of resources was still low, the facilities were inadequate, and staff appointments did not look at the dedication and ability and also did not the existence of standard operating procedures. The form of implementation of the Sumber Sustenance BUMDes policy is seen from the indicators of Communication, Resources, Disposition, and Bureaucratic Structure. Keywords: Policy Implementation, BUMDes